Improving seed quality in winter oilseed rape - Basu, Krishna Rachel (2003)
The majority of UK oilseed rape (Brassica napus L.) is September-sown on heavy clay soils where straw has been incorporated following the cereal harvest in August. A series of germination, emergence and field experiments was conducted to assess the effects of variation in seed quality on establishment and to evaluate the improvements possible by mother crop nitrogen management and pre-sowing seed treatments on commercial and farm-saved seedlots. In germination experiments designed to examme the performance of commercial seed lots at temperatures ranging between 5 and 25°C significant differences were recorded in the speed and unifonnity of germination, particularly at 10 and 15°C, which are comparable to UK field temperatures in late-August to September. The analysis of Apex variety seeds grown from nitrogen-managed mother crops in 1996 and 1998 showed a negative correlation between their nitrogen and oil percentage, which was significantly affected by both the amount (kg ha -1) and timing (vegetative growth period or flowering period) of nitrogen application. The highest nitrogen seeds were produced from mother crops that had received medium (160 kg ha -1) amounts of nitrogen fertiliser during the flowering period. Seeds that were harvested from pods taken from the lower < 1.5 m) section of the crop canopy also had a significantly higher nitrogen and significantly lower oil percentage than those taken from the upper (> 1.5 m) section of the canopy. In germination and emergence experiments the highest nitrogen (3.46 to 3.61 %) seeds germinated significantly faster than the seeds of lowest nitrogen (2.30 to 2.95%) content but they did not emerge as well as low nitrogen seeds from depth. Selecting small (< 2 mm diameter) seeds over large (> 2 mm diameter) seeds significantly improved the rate of geTI11ination and emergence and the final percentage emergence at 10 mm sowing depth although the final percentage emergence at 20 mm sowing depth was significantly greater from the large seeds. Hydrating seeds in water for 18 hours at 15 grad. C before drying them back in the laboratory at 20 grad. C significantly improved the speed of germination and the speed and final percentage emergence at 10 mm sowing depth compared with control treatments provided that the radicle had not emerged before drying back; small seeds derived the most benefit from hydration. Seed heat treatment at temperatures of 80 grad. C significantly delayed the onset of germination and emergence but significantly hastened field establishment. The effects of seed nitrogen percentage, seed size and heat treatment on seedling emergence and subsequent plant growth and development were examined in the field between October 1999 and July 2000. Growth analyses, which were performed in February (growth phase), May (flowering) and July (pre-harvest), showed that the high nitrogen, large seeded and heat-treated populations had a significantly lower rate of plant loss than the low nitrogen, small seeded and control populations. Under field conditions, the higher growth rates and growth parameters of the seedlings produced from the high nitrogen and! or large seeds were not always significant nor were they consistently maintained until harvest. Large seed size and heat treatment significantly increased the number of established plants per m2 and significantly increased the initial plant size. The final yield was not significantly affected by seed nitrogen percentage, seed size or seed heat treatment.